2019
DOI: 10.3390/nu11040764
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities in the Association between Cereal Consumption and Metabolic Syndrome: Results from the China Health and Nutrition Survey

Abstract: This study examines regional disparities in the association between cereal consumption and metabolic syndrome (MetS) among Chinese adults. We used data from the longitudinal China Health and Nutrition Survey (CHNS) for 2892 healthy adults aged 18–75 years (1088 in northern China, 1804 in southern China) who had no non-communicable chronic diseases or MetS at the initial visit in 2009 and the follow-up in 2015. We used a 74-item food frequency questionnaire (FFQ) to assess the dietary intake. We defined MetS ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Our study revealed that higher plasma DHPPA concentration was associated with lower OR of MetS, which also con rmed previous epidemiological studies used dietary recording methods to estimate whole-grain intake (26)(27)(28)(29). In the Framingham Offspring Cohort, whole-grain intake assessed via 126item Food frequency questionnaires (FFQs) was inversely related with the prevalence of MetS (26).…”
Section: Discussionsupporting
confidence: 88%
“…Our study revealed that higher plasma DHPPA concentration was associated with lower OR of MetS, which also con rmed previous epidemiological studies used dietary recording methods to estimate whole-grain intake (26)(27)(28)(29). In the Framingham Offspring Cohort, whole-grain intake assessed via 126item Food frequency questionnaires (FFQs) was inversely related with the prevalence of MetS (26).…”
Section: Discussionsupporting
confidence: 88%
“…Northern subjects consumed more sodium from flour products than southern subjects, which may be attributed to northern adults' preference for noodles and bread. A longitudinal study of Chinese adults found that the consumption of flour products in the northern area was more than twice that in the southern area [36]. Thus, for northerners, public health education should be implemented to raise awareness of the effects of sodium in flour products, which will help to reduce the total dietary sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…The CHNS and the survey procedure has been described in detail elsewhere [9,10]. Based on the natural boundary of a line along the Qinling Mountains and the Huaihe River, China is divided into North China and South China geographic areas [11]. All the analyses in this study were based on the data from 2009, 2011, and 2015.…”
Section: Study Design and Subjectsmentioning
confidence: 99%